2011
DOI: 10.1038/bmt.2011.95
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of hemophagocytosis in BM clot sections during the peri-engraftment period following allogeneic hematopoietic SCT

Abstract: The effects of macrophage activation on the outcome of allogeneic hematopoietic SCT (allo-HSCT) have yet to be fully examined. A total of 70 adult patients who received a first allo-HSCT for hematological diseases were studied. We counted the number of hemophagocytic cells in BM clot sections on day þ 14±7, and analyzed its impact on subsequent outcome. In all, 23 patients were diagnosed as having increased numbers of hemophagocytic cells (HP group), whereas 47 were not (non-HP group). The HP group was not ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…CD163-positive macrophages in the skin and bone marrow have been associated with refractory acute GVHD and poor prognosis. 34, 35 Thus CD163 concentrations might have been strongly influenced by the prior onset of acute GVHD and its treatment, and could have obscured any association with subsequent quiescent-onset cGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…CD163-positive macrophages in the skin and bone marrow have been associated with refractory acute GVHD and poor prognosis. 34, 35 Thus CD163 concentrations might have been strongly influenced by the prior onset of acute GVHD and its treatment, and could have obscured any association with subsequent quiescent-onset cGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…However, hemophagocytes are not essential to the diagnosis of HLH 3 , and can be seen in juvenile arthritis patients without overt MAS 4 . Additionally, hemophagocytes are found commonly in a host of other inflammatory states including sepsis 5 and following bone marrow transplant 6 . Whether hemophagocytes are inflammatory, anti-inflammatory, or serve different roles in differing diseases is a matter of ongoing study.…”
Section: The Final Common Pathwaymentioning
confidence: 99%
“…Further studies are needed in this area. In a clinical setting, Imahashi et al evaluated BM clot sections from 70 patients who received a first allogeneic HSCT and diagnosed 23 (33%) of the patients with hemophagocytosis; they suggested that early macrophage activation was a relatively common but unrecognized complication of allogeneic HSCT [28]. We and others also previously showed that hemophagocytosis is required for IL-10 production [15,16] by monocytic dendritic cells and that blocking hemophagocytosis or monocytic dendritic cellederived IL-10 significantly increases cytotoxic lymphocyte activity, tissue damage, and mortality in virus-infected hosts [16].…”
Section: Discussionmentioning
confidence: 99%